Estimation of Daily Sodium and Potassium Excretion Using Spot Urine and 24-Hour Urine Samples in a Black Population (Benin) - Mizéhoun-Adissoda, Carmelle; HOUEHANOU-SONOU, CORINE; Chianea, Thierry; Dalmay, François; Bigot, André K.; Preux, Pierre-Marie; Bovet, Pascal; Houinato, Dismand; Desport, Jean-Claude (My University, 2016)
The 24-hour urine collection method is considered the gold standard for the estimation of ingested potassium and sodium. Because of the impracticalities of collecting all urine over a 24-hour period, spot urine is often used for epidemiological investigations. This study aims to assess the agreement between spot urine and 24-hour urine measurements to determine sodium and potassium intake. A total of 402 participants aged 25 to 64 years were randomly selected in South Benin. Spot urine was taken during the second urination of the day. Twenty-four-hour urine was also collected. Samples (2-mL) were taken and then stored at -20°C. The analysis was carried out using potentiometric dosage. The agreement between spot urine and 24-hour urine measurements was established using Bland-Altman plots. A total of 354 results were analyzed. Daily sodium chloride and potassium chloride urinary excretion means were 10.2±4.9 g/24 h and 2.9±1.4 g/24 h, respectively. Estimated daily sodium chloride and potassium chloride means from the spot urine were 10.7±7.0 g/24 h and 3.9±2.1 g/24 h, respectively. Concordance coefficients were 0.61 at d=−0.5 g, (d±2SD=−11 g and 10.1 g) for sodium chloride and 0.61 at d=−1 g, (d±2SD=−3.8 g and 1.8 g) for potassium chloride. Spot urine method is acceptable for estimating 24-hour urinary sodium and potassium excretion to assess sodium and potassium intake in a black population. However, the confidence interval for the mean difference, which is too large, makes the sodium chloride results inadmissible at a clinical level.
Keywords: Estimation; Sodium; Potassium